FOOD PREFERENCE CHANGES BIOCHEMISTRY IN MOTHS LARVAE - GAUTAMI, R.K.; GAUTAM, SHIVARTI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
The study made on the alimentary canals of three different moths larvae showed the fate of total lipids, proteins, carbohydrates and moisture contents, which resulted into significant correlation to their food preferences.